2018
DOI: 10.1016/j.scitotenv.2017.08.136
|View full text |Cite
|
Sign up to set email alerts
|

The influence of permanently submerged macrophytes on sediment mercury distribution, mobility and methylation potential in a brackish Norwegian fjord

Abstract: Macrophytes are shown to affect the microbial activity in different aqueous environments, with an altering of the sediment cycling of mercury (Hg) as a potential effect. Here, we investigated how a meadow with permanently submerged macrophytes in a contaminated brackish fjord in southern Norway influenced the conditions for sulfate reducing microbial activity, the methyl-Hg (MeHg) production and the availability of MeHg. Historically discharged Hg from a chlor-alkali plant (60-80tons, 1947-1987) was evident th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…There is also a small outlet in the other end of the fjord through a small channel, built as an exit from the Gunneklev fjord into the Inner Grenlandsfjord for small recreational boats from the marina situated in the inner part of the Gunneklev fjord. The Gunneklev fjord is a brackish fjord (salinity 5-20 PSU in the bottom water (Olsen et al (2018) and references therein) with an average depth of 4.6 m and water volume of 3.5 × 10 6 m 3 . It is one of the most polluted fjord systems in Norway due to historic release of Hg-containing sludge from a chlor-alkali plant (Olsen et al 2018).…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…There is also a small outlet in the other end of the fjord through a small channel, built as an exit from the Gunneklev fjord into the Inner Grenlandsfjord for small recreational boats from the marina situated in the inner part of the Gunneklev fjord. The Gunneklev fjord is a brackish fjord (salinity 5-20 PSU in the bottom water (Olsen et al (2018) and references therein) with an average depth of 4.6 m and water volume of 3.5 × 10 6 m 3 . It is one of the most polluted fjord systems in Norway due to historic release of Hg-containing sludge from a chlor-alkali plant (Olsen et al 2018).…”
Section: Study Sitementioning
confidence: 99%
“…The Gunneklev fjord is a brackish fjord (salinity 5-20 PSU in the bottom water (Olsen et al (2018) and references therein) with an average depth of 4.6 m and water volume of 3.5 × 10 6 m 3 . It is one of the most polluted fjord systems in Norway due to historic release of Hg-containing sludge from a chlor-alkali plant (Olsen et al 2018). Previous studies have shown sediment concentration ranges of total mercury (THg) ranging from 2 to 5 mg kg −1 at the 0-5 cm surface layer to 500 mg kg −1 at 10-20 cm depth, and MeHg of 1-3 µg kg −1 at the surface to 300 µg kg −1 at 10-20 cm depth (Olsen et al 2018).…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…This fact confirms possible problems related to the presence of a high algal biomass in this ecosystem that could increase the process of Hg-methylation. MeHg production in macrophyte habitats in presence of Hg contaminated sites request more attention, with regards to the factors controlling the methylation processes (Olsen et al, 2018).…”
Section: Figurementioning
confidence: 99%
“…Seagrass meadows are known to trap particles from the water column 19,20 , thus enhancing sediment deposition and reducing resuspension 21 and are therefore suspect to high concentrations of contaminants within polluted areas. Accordingly, submerged meadows may be important exposure sites for contaminants to inhabiting organisms, and recent studies have shown enhanced bioavailability of sediment Hg within vegetated areas [22][23][24] , which may initiate a transfer of contaminants through food webs, with a potential to biomagnify at each trophic level. Thus, ecologically important submerged meadows within polluted areas potentially face the duality of being suspect to both remediation and conservation, which actualises the need to develop low-impact risk-reducing remediation strategies.…”
Section: Introductionmentioning
confidence: 99%